Quo vadis, euroland? European Monetary Union between crisis and reform - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2011)
This lecture discusses the 2010 crisis of the European Monetary Union and draws some lessons for reform. Crisis resolution has been difficult because the sovereign debt crisis of countries like Greece and Portugal has come together with real-estate and banking crises in countries like Ireland and Spain and bank vulnerability in countries like Germany and France. Failure to disentangle and resolve the different crises prevents a satisfactory approach to the long-term reform of governance of sovereign borrowing and banking. Any such reform must find a substitute for the discipline that exchange rate mechanisms impose on sovereign borrowers and their lenders when the currency is national. Any mechanism for imposing discipline on sovereign borrowers and their lenders must be designed so that enforcement is credible even in a crisis. Recommendations for reform include (i) an inclusion of sovereign exposure from too-big-to-fail concerns in banking in monitoring of fiscal stance, (ii) independence of bank supervisors from their respective political authorities, and (iii) a strengthening of the powers of the European Supervisory Authorities over the national supervisors.
Keywords: G28; F53; F33; F36; 330; European Monetary Union; sovereign debt crisis; bank supervision; Öffentliche Schulden; Staatsbankrott; Finanzmarktkrise; Bankenkrise; Europäische Wirtschafts- und Währungsunion; EU-Stabilitätspakt; Bankenpolitik; Bankenaufsicht; EU-Politik; Eurozone; EU-Staaten